2012
DOI: 10.1016/j.asw.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assessment, tutor mediation and academic writing development

Abstract: Supporting undergraduate students with their academic literacies has recently been a major focus in higher education in the UK. This paper explores the value of tutor mediation in the context of academic writing development among undergraduate business studies students in open and distance learning, following the Dynamic Assessment (DA) approach that has been developed within Vygotskian sociocultural theory of learning (Vygotsky, 1978). DA is an assessment approach that blends instruction and assessment. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 25 publications
9
65
0
3
Order By: Relevance
“…Second, previous DA research has been applied in various L2 contexts, such as learning French verbal aspect (Poehner 2008), Spanish grammatical concept of aspect (Prospero 2012) and English listening comprehension (Hidri 2014). However, only a few studies (Panahi et al 2013;Shrestha and Coffin 2012) have utilized DA to assess writing performance. Moreover, little research has applied DA in the context of learning Eastern languages, such as Chinese.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Second, previous DA research has been applied in various L2 contexts, such as learning French verbal aspect (Poehner 2008), Spanish grammatical concept of aspect (Prospero 2012) and English listening comprehension (Hidri 2014). However, only a few studies (Panahi et al 2013;Shrestha and Coffin 2012) have utilized DA to assess writing performance. Moreover, little research has applied DA in the context of learning Eastern languages, such as Chinese.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Twelve years later Maxwell (1990: 3) points out that a well-trained tutor can serve a vital role in helping fellow students attain their academic goals. Similar views are echoed by Brindley and Scoffield (1998) who found that peer assessment enabled students to better understand the assessment process; Fouche (2007) whose study determined that attending academic literacy tutorials had an influence on students' writing ability; Longfellow et al (2008) whose findings suggest that peer-assisted learning enables students to become better learners and Shrestha and Coffin (2012) who conclude that tutor mediation is an effective way to support students academic writing development. These and other studies highlight the value of tutor or peer-assisted learning.…”
mentioning
confidence: 75%
“…The idea of peer or tutor-assisted learning has its roots in the work of Vygotsky's sociocultural theory (SCT) and his concept of the zone of proximal development (ZPD) (Vygotsky, 1978;Van der Stuyf, 2002;Bodrova & Leong, 1998;Shrestha & Coffin, 2012). In SCT human cognition and learning do not take place in isolation, but rather occur "through participation in social or culturally embedded experiences" (Raymond, 2000:176).…”
mentioning
confidence: 99%
“…Researchers (e.g. Shrestha & Coffin, 2012;Christmas, Kudzai & Josiah, 2012;Chanyalew & Abiy, 2015) explained that learners develop their learning and understand the concept through adult guidance and mediate by capable peers and teachers. Similarly in dynamic assessment approach, students are mediated by their peers and the teacher, and students able to engage in every assessment procedures.…”
Section: Dynamic Criteria Mapping Assessmentmentioning
confidence: 99%